The Immune Checkpoint BTLA in Oral Cancer: Expression Analysis and Its Correlation to Other Immune Modulators - Ries, Jutta; Trumet, Leah; Hahn, Alina; Kunater, Lina; Lutz, Rainer; Geppert, Carol-Immanuel; Kesting, Marco Rainer; Weber, Manuel (International Journal of Molecular Sciences, 2024)
In oral squamous cell carcinoma (OSCC) tissues, an immunotolerant situation triggered by immune checkpoints (ICPs) can be observed. Immune checkpoint inhibitors (ICIs) against the PD1/PD-L axis are used with impressive success. However, the response rate is low and the development of acquired resistance to ICI treatment can be observed. Therefore, new treatment strategies especially involving immunological combination therapies need to be developed. The novel negative immune checkpoint BTLA has been suggested as a potential biomarker and target for antibody-based immunotherapy. Moreover, improved response rates could be displayed for tumor patients when antibodies directed against BTLA were used in combination with anti-PD1/PD-L1 therapies. The aim of the study was to check whether the immune checkpoint BTLA is overexpressed in OSCC tissues compared to healthy oral mucosa (NOM) and could be a potential diagnostic biomarker and immunological target in OSCC. In addition, correlation analyses with the expression of other checkpoints should clarify more precisely whether combination therapies are potentially useful for the treatment of OSCC. A total of 207 tissue samples divided into 2 groups were included in the study. The test group comprised 102 tissue samples of OSCC. Oral mucosal tissue from 105 healthy volunteers (NOM) served as the control group. The expression of two isoforms of BTLA (BTLA-1/2), as well as PD1, PD-L1/2 and CD96 was analyzed by RT-qPCR. Additionally, BTLA and CD96 proteins were detected by IHC. Expression levels were compared between the two groups, the relative differences were calculated, and statistical relevance was determined. Furthermore, the expression rates of the immune checkpoints were correlated to each other. BTLA expression was significantly increased in OSCC compared to NOM (pBTLA_1 = 0.003; pBTLA_2 = 0.0001, pIHC = 0.003). The expression of PD1, its ligands PD-L1 and PD-L2, as well as CD96, were also significantly increased in OSCC (p ≤ 0.001). There was a strong positive correlation between BTLA expression and that of the other checkpoints (p < 0.001; ρ ≥ 0.5). BTLA is overexpressed in OSCC and appears to be a relevant local immune checkpoint in OSCC. Thus, antibodies directed against BTLA could be potential candidates for immunotherapies, especially in combination with ICI against the PD1/PD-L axis and CD96.
CRIS-Team Scopus Importer:2024-07-12
Keywords: BTLA; CD96; immune checkpoints; immune therapy; oral squamous cell carcinoma; OSCC; PD-L1; PD-L2; PD1